2007
DOI: 10.1158/0008-5472.can-07-2485
|View full text |Cite
|
Sign up to set email alerts
|

Night Shift Work and the Risk of Endometrial Cancer

Abstract: Melatonin has several oncostatic properties, including possible anti-estrogenic and anti-aromatase activity, and seems to be linked with fat metabolism. Night workers have lower levels of melatonin, which may predispose them to develop cancer. Endometrial cancer risk is influenced significantly by hormonal and metabolic factors; therefore, we hypothesize that night workers may have an increased risk of endometrial cancer. Of the 121,701 women enrolled in a prospective cohort study, 53,487 women provided data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
181
1
5

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(191 citation statements)
references
References 30 publications
4
181
1
5
Order By: Relevance
“…We also found that ever night workers were more likely to have used exogenous hormones. Few other studies have reported on exogenous hormone use among night-working women, although ever use of HRT was found to be less common among rotating night shift workers in the Nurses' Health Study, particularly among long-duration night workers (15). Given the established effects of the reproductive and hormonal factors on the risk of breast cancer (16)(17)(18), the differences observed in the current study would put ever night workers, and especially long-duration night workers, at an increased risk of the disease.…”
Section: Wang Et Almentioning
confidence: 86%
“…We also found that ever night workers were more likely to have used exogenous hormones. Few other studies have reported on exogenous hormone use among night-working women, although ever use of HRT was found to be less common among rotating night shift workers in the Nurses' Health Study, particularly among long-duration night workers (15). Given the established effects of the reproductive and hormonal factors on the risk of breast cancer (16)(17)(18), the differences observed in the current study would put ever night workers, and especially long-duration night workers, at an increased risk of the disease.…”
Section: Wang Et Almentioning
confidence: 86%
“…The IARC review further stated that the association between shift work and breast cancer was supported by sufficient evidence among experimental animals but only limited evidence in epidemiological studies on humans. Regarding cancer, shift work has been associated with breast cancer (5,6,7), prostate cancer (8), endometrial cancer (9), colorectal cancer (10), and Non-Hodgkin's lymphoma (11). The most extensively studied cancer in this context is female breast cancer.…”
mentioning
confidence: 99%
“…A causal link between shift work and cancer has such strong supporting evidence that shift work has been classified as a "probable carcinogen" (19). Besides colorectal cancer, there are many reports about a relation between shift work and endometrial, prostate, and breast cancer (20)(21)(22). Exposure to light at nighttime suppresses melatonin production.…”
Section: Statistics For Night Shifts and Do Night Shifts Lead To Healmentioning
confidence: 99%
“…This treatment is effective, especially in elderly people; the response is at the moderate level in young individuals. For this purpose, the patient is exposed for 1-2 h (between 19:00 and 21:00) to bright blue light (2500-10000 lux) (20). If the patient needs to receive light during the daytime, he/she is exposed to 2500-5000 lux for 2 daytime hours for a duration of 4 weeks (Figure 1).…”
Section: What Are the Other Treatments For Sleep Disorders?mentioning
confidence: 99%